THE RISE OF E-FINANCING: PATHWAYS TO MODERNIZATION IN PAKISTAN’S FINANCIAL SECTOR - Malik, Ahmed Farooq; Shah, Sarah Nasreen (Ayden Journal of Management and Social Sciences, 2024)
The usage of plastic money, such as debit cards and credit cards, has significantly increased in recent years, revolutionizing the way transactions are conducted. Unlike traditional paper money, plastic money is made from durable plastic material, providing enhanced security and convenience for customers. Plastic money includes various forms of cards, like debit cards, credit cards, ATM cards, and smart cards, each offering distinct benefits and features (Mutual E, 2001). Plastic money has gained widespread acceptance due to its efficiency in facilitating quick and secure payments. Cards bearing the Visa and MasterCard logos are recognized and accepted worldwide, making them a convenient choice for consumers (Connie Prater, 2008). Credit cards enable individuals to make purchases using the bank's funds, while debit cards allow for transactions using the cardholder's own money. Despite the growing popularity of plastic money, certain challenges persist, particularly in countries like Pakistan. Factors such as frequent electricity breakdowns, concerns about theft and fraud, and high levels of illiteracy, especially in smaller cities, have limited the widespread adoption of plastic money. The financial sector, with increased competition among institutions, has recognized the growing demand for plastic money in countries like Pakistan. This paper explores the evolving landscape of plastic money usage, the challenges it faces, and its potential impact on the financial sector, with a focus on the Pakistani context.